Clubs and Networks in Economic Reviewing - Scott Carrell; David Figlio; Lester Lusher (Institute for Replication (I4R), 2023)
We study how author-editor and author-reviewer network connectivity and "match" influence editor decisions and reviewer recommendations of economic research at the Journal of Human Resources. Our empirical strategy employs several dimensions of fixed effects to overcome concerns of endogenous assignment of papers to editors and reviewers. Authors who attended the same PhD program, were ever colleagues with, are affiliates of the same National Bureau of Economic Research program(s), or are more closely linked via coauthorship networks as the handling editor are significantly more likely to avoid a desk rejection. Likewise, authors from the same PhD program or who previously worked with the reviewer are significantly more likely to receive a positive evaluation. We also find that sharing "signals" of ability, such as publishing in the "top five", attending a high ranked PhD program, or being employed by a similarly ranked economics department, significantly influences editor decisions and/or reviewer recommendations. We find some evidence that published papers with greater author-editor connectivity subsequently receive fewer citations.
Keywords: 330